Business success factors of Latvian and Swedish forestry contractors. Issue 3 (2nd September 2022) - Gercans, Janis; Kons, Kalvis; Kronholm, Thomas
ABSTRACT: The economic viability of forestry contractors is a long-term topic of debate among forest sector professionals and researchers. The forestry contractor business depends heavily on the primary buyers of their services, with a plethora of factors influencing successful business. A survey of 110 forestry contractors from Latvia (LVA) and Sweden (SWE) indicate that the skillfulness of employees, teamwork, good collaboration with business partners, treatment of employees, demand, favorable weather conditions, quality of work, good contract rates, investment in new machinery, and experience in the sector were important factors for success in the forestry contractor business. However, there are differences between the two countries in business-influencing factors. Entrepreneurial orientation (EO) and financial indicators such as net turnover, net profit, return on assets, return on sales, and the number of employees were significantly higher for LVA forestry contractors. At the same time, net profit per employee and net turnover per employee were` significantly higher for SWE forestry contractors.